Pengaruh Motivasi Kerja dan Pengembangan Karir terhadap Promosi Jabatan di Polsek Bajubang Kabupaten Batanghari - Etty Siswati; Evi Fauzani; Karyadi Karyadi (Universitas Batanghari Jambi, 2019)
This study aims to determine the effect of (X1) Work Motivation, (X2) Career Development on (Y) Job Promotion Di Polsek Bajubang Kabupaten Batanghari. This research is a quantitative descriptive study. The sample of this study was 31 people. Based on the results of research and discussion, then some of the main points of research conclusions can be explained as follows. Based on the results of the partial test (t test). Obtained tcount for (X1) Work Motivation is 10,032 and ttable value is 1.69913 because tcount is smaller than ttable so it can be concluded that work motivation does not significantly influence employee performance. Whereas (X2) Career Development, the value of tcount is 5,977 and the value of t table is 1,69913 because tcount is greater than ttable, it can be concluded that work discipline has a significant effect on employee performance. Based on the results of the Simultaneous Test (Test F). Obtained Fcount value of 19,379 and Ftable value of 3.93 because the Fcount value is greater than Ftable, it can be concluded that work motivation, work discipline and work competence show a significant influence on employee performance. Based on the results of the Coofesien Determination (R2) obtained an Adjusted R Square value of 551, it can be concluded that the percentage influence of Work Motivation (X1 ), Career Development (X2) on Performance (Y) of 55.1% and 44.9% is influenced by other variables not examined in this study.